Prevalence and Risk Factors of Asthma in School Going Children in South India - Mathew, Anil Chankaramangalam; Prince, TG; Remees, R; Saravanapandian, N; Ramalingam, S; Srikanth, K; Mathai, J (Nepal Journal of Epidemiology, 2012)
Background In India, the prevalence of asthma has increased over the last two decades especially in children and young adults. The aim of the study was to estimate the prevalence of asthma in school going children aged 5-10 and 11-15 years in the city of Coimbatore and determine the risk factors associated with it. Materials and methods A school based cross-sectional study was conducted at the urban field practice area of PSGIMSR, Coimbatore between 1st June 2011 and 31st August 2011. The questionnaire was filled by the parents and collected from the children. The data were analyzed using SPSS (11.5version). Results The prevalence of asthma among children aged 5-10 years was 9.5% (95% Confidence Interval (CI) 7.49 – 11.50) and among children aged 11-15 years was 7.27% (95% CI 5.40 – 9.14). The Risk factors significantly associated with asthma among children aged 5-10 years were positive family history of asthma (Odds Ratio (OR)=3.10, 95% CI 1.80 - 5.36), longer duration of time spent in front of television and computer (OR=2.75, 95% CI 1.44 - 5.25), having food allergies (OR=2.36, 95% CI 1.19 - 4.68), and low birth weight of the child (OR=1.79, 95% CI 1.08 - 2.98). The factors significantly associated with asthma among children aged 11-15 years were positive family history of asthma (OR=2.99, 95% CI 1.34 - 6.64), poor ventilation (OR= 4.94, 95% CI 2.72 – 8.93), and use of pillows made up of wool, foam or synthetic material (OR=2.7, 95% CI 1.31 - 5.58). Conclusion Our data suggests that there is a high prevalence of asthma among school going children in Coimbatore. Parental history of asthma was a risk factor in both age groups studied. Television viewing for more than 2 hours, low birth weight and food allergy are additional risk factors for children aged 5-10 years. Poor ventilation and use of pillows made up of wool/ foam/ synthetic material are other risk factors in 11-15 years old children. Appropriate preventive strategies may help reduce the risk of asthma. Children with low birth weight and a family history of asthma need careful evaluation and long term follow up. DOI: http://dx.doi.org/10.3126/nje.v2i1.6378 Nepal Journal of Epidemiology 2012;2 (1):171-178